2016
DOI: 10.1093/cercor/bhw150
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Object Size and Object Category in Human Visual Cortex

Abstract: A salient aspect of objects is their real-world size. Large objects tend to be fixed in the world and can act as navigational barriers and landmarks, whereas small objects tend to be moveable and manipulable. Previous work has identified regions of visual cortex that respond differentially to large versus small objects, but the role of size in organizing representations of object categories has not been fully explored. To address this issue, we scanned subjects while they viewed large and small objects drawn f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 63 publications
4
50
4
Order By: Relevance
“…This is notable because the PPA (or parahippocampal place area), which includes the posterior portion of PhC, has also been shown to have higher levels of activity for inanimate objects, even when contrasted with shape‐matched animate objects (Proklova, Kaiser, & Peelen, ). Moreover, a number of studies have demonstrated that the PPA is more active for large than for small objects (Konkle & Carmazza ; Aguirre et al, ; Julian et al, ) , and most similar to our findings, that patterns of activity in the PPA distinguish between large and small objects (Julian et al, ). This sensitivity to real‐world size in the PPA, as well as that in the PhC that we describe here, appears to be more reliable than what is observed in PrC, where it reflected only a trend in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is notable because the PPA (or parahippocampal place area), which includes the posterior portion of PhC, has also been shown to have higher levels of activity for inanimate objects, even when contrasted with shape‐matched animate objects (Proklova, Kaiser, & Peelen, ). Moreover, a number of studies have demonstrated that the PPA is more active for large than for small objects (Konkle & Carmazza ; Aguirre et al, ; Julian et al, ) , and most similar to our findings, that patterns of activity in the PPA distinguish between large and small objects (Julian et al, ). This sensitivity to real‐world size in the PPA, as well as that in the PhC that we describe here, appears to be more reliable than what is observed in PrC, where it reflected only a trend in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Inasmuch as the pattern of activity across voxels can be labeled a neural representation of an object, one can think of the comparisons between categories as now existing in “representational geometry.” Interestingly, Kriegeskorte et al () applied this approach to voxels distributed throughout the ventral temporal cortex using a wide variety of objects, and found a highly consistent category‐ and domain‐based organization, with evidence for a distinction between animate and inanimate objects, as well as varying degrees of similarity between categories within these domains (see also Proklova, Kaiser, & Peelen, ). A recent fMRI study with a similar focus on representational similarities has shown that real‐world size is also an organizing dimension of objects across a large swath of temporo‐parieto‐occipital cortex, and within a number of subregions across the VVS (Julian et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The approach of examining the high-level statistical regularities of objects and scenes may provide insight into longstanding questions about cortical function. In the case of scene-selective cortex, previous work has shown that scene regions respond to several high-level properties of objects, including contextual-association strength, real-world size, landmark suitability, spatial definition, and interaction envelope 11,21,[48][49][50] . Scene-selective regions also respond to several mid-level properties of images, including high spatial frequencies, rectilinearity, and cardinal orientations [51][52][53][54] .…”
Section: Natural Statistics and Cortical Representationmentioning
confidence: 99%
“…This is notable because the PPA (or parahippocampal place area), which includes the posterior portion of PhC, has also been shown to have higher levels of activity for inanimate objects, even when contrasted with shape-matched animate objects (Proklova, Kaiser, and Peelen, 2016). Moreover, a number of studies have demonstrated that the PPA is more active for large than for small objects (Konkle et al, 2013;Aguirre et al, 1998;Julian et al, 2016 ), and most similar to our findings, that patterns of activity in the PPA distinguish between large and small objects (Julian et al, 2016). This sensitivity to real-world size in the PPA, as well as that in the PhC more broadly that we describe here, appears to be more reliable than what is observed in PrC, where it reflected only a trend in the current study.…”
Section: Phcmentioning
confidence: 99%
“…A recent fMRI study with a similar focus on representational similarities has shown that realworld size is also an organizing dimension of objects across a large swath of temporo-parietooccipital cortex, as well as within a number of subregions across the VVS (Julian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%